Gender wage disparity and economic prosperity in Pakistan - Maria Faiq Javed (Cogent Economics & Finance, 2022)
The present study is designed to examine the relationship between wage inequalities and economic prosperity in the case of Pakistan. Using provincial-level data for the years 2000 to 2020, the study estimated a multivariate regression model by employing Auto Regressive Distributive Lag (ARDL) pooled mean group (PMG) technique. The results reveal that wage inequality, government development spending, labor force participation, and human development significantly affect economic prosperity. It is concluded that gender disparity in the labor market is the main hurdle in the economic wellbeing of the masses in the country. Reducing the differences in wages will enhance overall economic prosperity. The government and private sector should take collaborative measures to reduce wage disparities between the male and female workforce. The study also suggests that government should increase development expenditure, especially on health, education, and social infrastructure, to increase economic prosperity.